Land nationalization - Justin, Miner M. (My University, 1907)
Introduction: At no time in the history of the world has the product of human industry been so great as at the present. The fullest cooperation ever known and the ingenious machinery to be found in all branches of production applied to the almost limitless extent of natural resources make the work of the laborer more effective than ever before. Not only is production greater but the facilities for exchange were never so good as now. The most widely separated peoples have become neighbors commercially. Under such circumstances it is but natural that we should expect to find the misery and destitution so common among the lower classes during the middle ages, giving way to universal.comfort. But this is not the case. The poor have not become independent with the increase in the effectiveness of their labor. The squalor and misery in some of our cities today is so great that it seems impossible that a worse state ever existed. In these places twelve and fourteen hours of labor in a room where sunlight never strikes and fresh air is almost unknown for the smallest pittance which will keep them in existence is the daily lot of many. Many others while not so toil –burdened nor so poorly paid are unable to make any provision whatever for sickness or old age. To such as these the increase in their productive power seems a mockery and they' look with envy and bitterness on that class so distinctively modern, a product of the last century, the class whose wealth is measured by millions. The possessors of these colossal fortunes are, many of them, men who seem to have nothing to do but spend the wealth they have secured. They build grand palaces such as the despots of olden times with the wealth of empires behind them never equaled in magnificence:they have servants in greater numbers than ancient war barons had vassals:merely to outdo their fellows they give…
Citation: Justin, Miner M. Land nationalization. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Land Nationalization; Wealth Inequality; Social Class; Theses